ISSUES FOR FURTHER IMPROVEMENT OF THE INSTITUTION OF REVIEW OF JUDICIAL ACTS THAT HAVE ENTERED INTO LEGAL FORCE DUE TO NEWLY DISCOVERED CIRCUMSTANCES IN THE ECONOMIC PROCESS - Abidov Jasurbek Kosimovich (European Science Publishing, 2024)
This article highlights the concept, value, role and issues for further improvement of the institution of review of judicial acts that have entered into legal force due to newly discovered circumstances in the economic process and its place in the procedural legislation. In the article, examples from the legislation of foreign countries and judicial practice are given, opinions are expressed based on comparative legal analysis. The author analyzed the grounds for reviewing judicial acts on newly discovered circumstances and put forward proposals on this issue.
Keywords: Judicial acts, new or newly discovered circumstances, review, legal facts, appeal, cassation, supervision, transaction, constitutional Court.